Corruption under moral hazard - Eskeland, Gunnar S. 1959- (Policy research working paper, 1999)
Some corruption of employees will exist when managers are constrained in setting rewards and penalties. Attempts to reduce corruption need to address these constraints. Raising salaries without raising expected penalties will have higher costs than benefits